2006
DOI: 10.1086/498181
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Temperature and Light Alter the Flight Speed of Hornets (Vespa crabroL.)

Abstract: Although the principal mechanisms of insect flight are well understood, knowledge about the influence of environmental factors on flight performance is scarce. We show that ambient temperature (TA) and illuminance have an influence on the flight performance of hornets. Moreover, the regulation of flight speed at different environmental conditions is sex specific. In roundabout experiments with tethered hornets, the flight speed of workers was independent of TA, while that of drones was negatively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 27 publications
9
30
0
Order By: Relevance
“…Flight speed decreased more or less linearly in response to a logarithmic decrease in light intensity. This result is consistent with the findings of a previous study, which showed that tethered hornets fly slower in dim light (Spiewok and Schmolz, 2006). In that study, the flight speed of hornets was measured at three different light intensities, similar to the ones used in our study (850, 5 and 0.5 lx).…”
Section: The Effect Of Light Intensity On Flight Speed and Temporal Rsupporting
confidence: 93%
See 2 more Smart Citations
“…Flight speed decreased more or less linearly in response to a logarithmic decrease in light intensity. This result is consistent with the findings of a previous study, which showed that tethered hornets fly slower in dim light (Spiewok and Schmolz, 2006). In that study, the flight speed of hornets was measured at three different light intensities, similar to the ones used in our study (850, 5 and 0.5 lx).…”
Section: The Effect Of Light Intensity On Flight Speed and Temporal Rsupporting
confidence: 93%
“…Earlier experiments on vertebrates (Barlow, 1958), flies (Pick and Buchner, 1979), honeybees (Rose and Menzel, 1981;Chittka and Spaethe, 2007), hornets (Spiewok and Schmolz, 2006) and the nocturnal bee M. genalis (Theobald et al, 2007) have pointed towards higher order summation of visual signals as an adaptation for vision at low light levels. Such summation, along with the behavioural and retinal adaptations examined in this study, would enable foraging flights earlier in the morning and later in the evening, albeit with reduced efficiency -a cost that is probably worth paying in the competition for nectar and pollen.…”
Section: Photoreceptor Voltage Response Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the duration of each trip can be accurately quantified with RFID: 95% of the flights lasted less than 1 hr. Flying speeds of V. velutina workers are so far unknown, but in V. crabro , it has been estimated at 1.86 m/s (i.e., 6.7 km/hr) (Spiewok & Schmolz, 2005). If both species fly at a similar speed and considering the average trip duration being 15 min, V. velutina workers probably forage within less than 1,000 m away from their nest.…”
Section: Discussionmentioning
confidence: 99%
“…While differing less dramatically, the compound eyes of the nocturnal species are also relatively larger, and typically contain larger numbers of ommatidia, than those of their diurnal relatives (Jander and Jander, 2002). Interestingly, the common European hornet Vespa crabro, which has also been suggested to have nocturnal activity (Blackith, 1958;Spiewok and Schmolz, 2006), lacks all such optical enlargements (F. Jonsson, A. Kelber and E.J.W., in preparation).…”
Section: Nocturnality In Bees and Waspsmentioning
confidence: 99%